Philosophy Of Division of Authority of Regional Heads and Deputy Regional Heads in The System of Regional Government Administration - Hadita, Cynthia (Indonesian Journal Education, 2025)
The division of authority between regional heads and deputy regional heads in the system of local government administration is not only administrative, but also contains a deep philosophical dimension. The research method used is normative juridical with a philosophical approach. The results of the study show that, ontologically, the existence of the positions of regional head and deputy regional head is a manifestation of the principle of duality in leadership, where responsibility cannot be borne by one individual alone. Its epistemology reflects efforts to formulate a balanced and functional power structure, in order to achieve effectiveness in local government. Meanwhile, axiologically, this division of authority is based on the values of democracy, justice, and accountability, which aims to ensure that regional leadership can run collectively, not authoritarianly, and remain within the corridor of public services. However, in practice, the unclear boundaries of authority often lead to conflicts, functional inequality, and even government stagnation. Therefore, a philosophical and normative reformulation of the relationship of authority between regional heads and deputy regional heads is needed in order to create harmonious, effective, and people-oriented regional governance.